Analisis Pengaruh Pendidikan, Pertumbuhan Ekonomi dan Pendapatan Perkapita Terhadap Chronic Poverty - Tri Kurniawati; Erien Yuan Lestari (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2021)
This study objectives are to analyze: 1) the effect of education on chronic poverty in West Sumatra, 2) the effect of economic growth on chronic poverty in West Sumatra, 3) the effect of per capita income on chronic poverty in West Sumatra, 4) the effect of education, economic growth and per capita income on chronic poverty in West Sumatra. This is a quantitative research. This study used secondary data from 2010-2019, obtained from related institutions and agencies and then was analyzed by using multiple linear regression analysis. Prerequisite analysis tests performed include normality test, heteroscedasticity test, multicollinearity test and autocorrelation test. The results shows that 1) education has a negative and significant effect on chronic poverty in West Sumatera, 2) economic growth has a negative and significant effect on chronic poverty in West Sumatera, 3) per capita income has negative and insignificant effect on chronic poverty in West Sumatera, 4) education, economic growth and per capita income have significant effect on chronic poverty in West Sumatera simultaneously.